ANALISIS PENYERAPAN TENAGA PADA INDUSTRI KECIL DAN MENENGAH (Studi Kasus Pada Industri Kecil dan Menengah Furniture Kayu di Kabupaten Jepara) - Siburian, Vera Haryani; Woyanti, Nenik (Diponegoro Journal of Economics, 2013)
Industrialization is one of the goverment’s ways to increase the economical development, that the main goal is to give more chance to work. The efforts to recruit workers cannot be separated from some factors that have an effect on it, such as the growth of the population and workers, the economic development and the recruitment of worker and not to deny the other efforts that can raise higher productivity through any other programs. One of the ways to enlarge the recruitment of workers is by developing industry mainly industry which focuses on work production. Developing work production industries will raise the capacity of the production so it can make job oppotunities. Industrial Departement of Central Java, Jepara Regency’s data show that micro and middle industries are the most available and need the most employees in Jepara’s Regency is wood furnitue industries. The main goal of this researh is to analize the recruitment of employees at micro and middle wood furniture industries in Jepara’s Regency and also to find out the influence variables.The method of this analysis is multiple linear regression with double log method. Data that used in this research is based on premier data that got from directly interview with micro and middle wood furniture entrepreneurs at Jepara Regency belonging to prepared question list.The result of this research summarize that working capital has positive and significant influence for labor requirements of micro and middle wood furniture industry at Jepara’s Regency, labor’s productivity has positive and significant influence for labor requirements of micro and middle wood furniture industry at Jepara’s Regency, labor’s wage has negative and significant influence for labor requirements of micro and middle wood furniture industry at Jepara’s Regency and the business age has positive and significant influence for labor requirements of micro and middle wood furniture industry at Jepara’s Regency.